Custom-Made Foot Insoles on Dynamic Balance in Children with Flexible Flat Feet: A Community-Based Study - Nur Rachmat; Bambang Kuncoro; Dody Suprayogi; Atika Febri Anggraini; Annisa Dwi Nur Kusumawardani; Indra Yulianti (Jurnal Kesehatan Masyarakat, 2026)
Flexible flat feet in children are common in community and school-aged populations and may be associated with altered lower-limb biomechanics, impaired postural control, and reduced dynamic balance, potentially affecting mobility, participation, and safety in daily activities. Although custom-made foot insoles are widely prescribed, evidence regarding their functional effects on dynamic balance in community-based pediatric settings remains limited. This study aimed to evaluate the effects of custom-made foot insoles on dynamic balance among children with flexible flat feet in a community-based rehabilitation context. A pre–post intervention study was conducted involving 40 children (mean age 10.05 ± 1.04 years). Dynamic balance was assessed using the Balance Beam Test before and after the intervention. Changes in balance performance were analyzed using the Wilcoxon signed-rank test, with effect size calculated using Cohen’s d. Dynamic balance scores improved significantly after insole use (Z = −3.995, p < 0.001), with a large effect size (d = 0.81). Greater improvements were observed in children with lower baseline balance. These findings support the potential role of custom-made foot insoles within community-based rehabilitation strategies to enhance functional balance and promote safe participation among children.